British Public Opinion towards the Kurdish September Revolution 1961 - 1975, the British Times Newspaper as A Model - Malook, Fayza M. (Humanities Journal of University of Zakho, 2016)
September was the Kurdish revolution stemming from the genuine desire of the Kurdish people for change, and this was a correct path of the revolution as a return to the principles of the revolution in July 1958. It has resulted in the occurrence of clashes and negotiations with the Iraqi government. And has taken care of the international public opinion in general, the events of the revolution; the consequent international moves in all fields.In this study, the researcher will address a model of European public opinion models of the reality of what British newspaper wrote in The Times about the revolution. The study was important for British public because they were accused by the Iraqi government of supporting the rebels.In this study, the researcher will criticize what it wrote in The British Times newspaper not merely events listed; in order to stand on the seriousness of these writings being published in one of Britain’s biggest daily newspapers.